Tendency of the population aging and the elder groups’ people health in Tomsk Region - T. Yu. Lozhkina (Бюллетень сибирской медицины, 2009)
The statistical rates of population health both in Russian Federation and Tomsk Region demonstrate the high morbidity level among the persons from 60 years and older, which are three times and more exceeding the analogous rates of the employers. The predominance of chronic forms of pathologies among the elder age people, which are aggravated by the natural (physiological) aging processes, influence structural and quantitative components of health care system.